Trauma narratives double injury and the unstoppable effectiveness of schizoid-paranoid use of technology - mass rape, blunt hunger, organised crime and state terrorism - Lacerda-Nobre, Ângela; Gameiro, A.; Duarte, R.; Cunha-Lima, M. (Book of Abstracts for the 5th Social and Solidarity Economy and the Commons International Conference, 2025)
Trauma refers to the self-destructive blockage of life’s inner energy by the perpetuation of a justificatory and legitimising narrative, as whatever may cause pain, suffering and destruction will become structurally consolidated by the glue of the self-serving discursive social fabric. Schizoid-paranoid psychopathology, personality traits, decision-making trends and social regulation and control disorders are built upon survival lizard-brain para-sympathetic reactions. Political instrumentalization and manipulation can induce the legitimisation, normalisation and naturalisation of self-destructive positioning on a large scale. Technology has become the ultimate example of how human talent, proficiency and ingenuity may lose its purpose and engage in self-damaging deviant forms of intentionality. It is not a question of authenticity as the idealisation, abstraction and alienating process argutely becomes self-imposed individually and collectively, fuelled by messianic and apocalyptic perverted expectations. Truth, beauty, goodness, fairness or justice, whose cannons helped to calibrate different cultures and civilisations across humanity’s history, have themselves become instrumentalised, manipulated and put to the service of vested interests. The ubiquity of technology, from digital to quantum computing, Artificial Intelligence, AI and Large Language Models, LLM, imply that policy-making, governance and private-public spheres of action, regional and global, have become mutually contaminating. The present exponential rise and near collapsing increase of violence, material and symbolic, has become literally visible, expressed and broadcasted by both hunger and rape as warfare that are simultaneously archaic and hyper-modern, annunciating an age of terror and fear. If no social justice is possible without ecological justice, no technoscience development can occur without ethical, epistemic and political renewal. No facelifts, quick fixes, shortcuts or blame games can do the trick of reinventing a broken human world that has lost its humane core, but slow cooking and slow food exercises, practices and techniques can help restore hard to face reality. As in restorative justice, dealing with wrongdoing and focusing on repairing, on mitigating damages and on prevention is key. The argument is one of love. The rationale is that if it is not possible to love what one does not know exists then one has to know in order to love. That is, it is a to love-to know and a to know-to love impulse that must be reawakened, cherished and protected, fostering the best of human creativity and spontaneity. Creating and supporting safe and secure spaces for discussion, debate and confrontation of ideas, in academia, in civil society and in the political fora, within the military and policing forces, among international trade negotiations and juridical and law enforcing institutions, through the old and the new media, addressing and denouncing organised crime and state terrorism is the core of an open science agenda for social and democratic renewal. Democracy and freedom are living ideals and not void elements of discursive electoral practices. The scientific areas of International Relations and of Public Relations, by denouncing, announcing and proscribing self-destruction and by promoting humane relations and Nature-based relations, can help shift the balance towards much needed social change. The power of phenomenological intentionality and inquiry can be inspired by authors including Maine de Biran, Michel Henry, Jacob Levy Moreno, Catherine Malabou, Katharina Pistor and Bonnie Mann. Some of the living examples from Global North and from the Global South, are a continual and ongoing source of inspiration and guidance, including intentional communities, the Global Ecovillages Network, the Agroecology movement, the Transition Towns movement, the Regenerative development movement, the Degrowth and Fair-Trade movements, the Extinction Rebellion and the Scientists Rebellion movements and the platforms such as MAD Africa, Maakum Ceuta, Outras Palavras and DiEM25. Anti-philosophy philosophy and anti-psychiatry psychiatry intellectual schools of thought of the previous two centuries have become fertile ground for unveiling, revealing and announcing possible breakthroughs related to the essence of what it means to be human and to collectively organise action as a form of democratic and freedom exercise. Exploring shadows and luminous realities is a possible health test check whose didactic purposes may help to reconcile human’s vulnerabilities, frailties, incompleteness and finitude and reawaken an age of abundance, generosity and plentifulness for all, human and beyond human alike.